Axiological Approach and Foundations of strategic Goal-setting in the context of the Digital Transformation of the Economy and Management - O. M. Pisareva (Модернизация, инновация, развитие)
Purpose: the purpose of the research is to determine the essence and role of the value approach to setting and solving goal-setting tasks in the system of state strategic planning in conjunction with the analysis of the correlation of goals and interests of economic agents in the conditions of realization of property rights to natural and intellectual resources of the development of the social state.Methods: the issues of identifying the essence and studying the characteristics of the axiological foundations of goals-setting for national development in the sphere of public power, as well as determining the motivational role of ownership relations in the initiation and coordination of purposeful activities are considered using the methods of logical, content and statistical analysis in the framework of a systematic approach to the study of problems and tasks of improving the methodology and tools of strategic planning in the conditions of digital transformation of society, economy and management.Results: the issues of improving the goal-setting mechanism in the context of reforming the state strategic planning system of the Russian Federation in the context of digital transformation of the economy and management are considered. Assessments of the validity and effectiveness for setting and achieving goals in strategic planning documents in the framework of development programming at the federal, regional and municipal levels of government are presented. The state of institutional support for the tasks of setting goals of socio-economic development in the multi-level structure of public administration bodies is characterized. Axiological aspects of targeting coordinated activities in various types of organizational systems are described. The article analyzes the features and role of ownership rights to natural and intellectual resources by the implementation of the concept of sustainable development in the social state. The features of the implementation of property rights to natural and intellectual resources in the context of the implementation of the concept of sustainable development of the social state are analyzed. The role of property relations in the initiation and coordination of purposeful activity of economic agents in the space of national development has been determined.Conclusions and Relevance: The results of the study allow us to formulate a number of conclusions. Firstly, further improvement of the methodology of strategic management should be carried out in the context of the interrelated modernization of national models of economy, development and management. Secondly, the advance of methods and tools for substantiating long-term development goals should take into account the axiological foundations of goal-setting. And third, digital transformation allows to differentially describe the motivational function of public ownership by natural and intellectual resources of development.